Perinatal outcomes in preterm premature rupture of membranes - Chuvakova, T.; Bapayeva, G.; Issayeva, R.; Begimbetova, D.; Olzhayev, F.; Dzhamanaeva, K.; Kenbaeva, K. (Personalized medicine and Global Health, 2015)
Preterm premature rupture of membranes (PPROM) is one of the leading causes of perinatal morbidity and mortality. Intrauterine continuous amnioinfusion via a subcutaneously implanted port system for PPROM is an attempt to improve the perinatal outcomes.
2 nd International conference "Personalized medicine and Global Health"
Keywords: preterm premature rupture of membranes; perinatal mortality; perinatal morbidity